PENGARUH MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT BENTORO ADISANDI IVENA BATAM - Heryitno, Ayit; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2022)
For long term, the company's purpose is usually to searching for income and try and survive. For make it appear, the business enterprise makes use of production elements consisting of generation, labor competencies and capital to carry out sports. Human capital additionally plays an vital position in the organisation as thinkers, planners. Many elements affect worker performance, which include motivation and compensation. employee reimbursement need to have a valid logical foundation. The venture of this observe become to evaluate whether or not paintings motivation and work motivation have a partial or simultaneous impact at the place of business of PT Bentoro Adisandi Ivena Batam. This look at has a pattern of one hundred twenty samples whose information have been amassed and then analyzed thru SPSS model 25. The effects of this have a look at show that work engagement can have a tremendous and partial impact on worker overall performance of PT Bentoro Adisandi Ivena Batam, compensation has a sizable impact partly fantastic and sizable on the performance of employees of PT Bentoro Adisandi Ivena Batam, as well as work motivation and reimbursement at the same time as it has a positive and sizable effect on worker overall performance of PT Bentoro Adisandi Ivena Batam.